The medaka mutation tintachina sheds light on the evolution of V-ATPase B subunits in vertebrates - Loosli, Claudia; Wittbrodt, Joachim (Scientific reports, 2013)
Vacuolar-type H+ ATPases (V-ATPases) are multimeric protein complexes that play a universal role in the acidification of intracellular compartments in eukaryotic cells.